2018
DOI: 10.1590/0102-7786332007
|View full text |Cite
|
Sign up to set email alerts
|

Wind Power in Girau do Ponciano, Alagoas, Brazil Using Anemometric Data and Microscale Modeling

Abstract: The wind potential in the Agreste region of Northeastern Brazil has important features for energy exploration, but, stills unexplored. This work analyzes 3.1 yrs anemometer tower measurements in the Girau do Ponciano, Alagoas state. The observational data was recorded from October 2007 to October 2010. Three periods were defined to constrain the seasonal wind patterns: Annual, Dry (October-January) and Wet (May-August). Hourly and monthly series showed the average wind speed was higher than 7 m s-1, reaching 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
5
0
3
Order By: Relevance
“…The parameter c, in general, was close to 3 ms -1 (10 m) and 4 ms -1 (100 m). Analyses carried out by Ramos et al (2018) show distribution patterns as positive examples for eolic energy generation, as they detect only minor problems with the change of the wind (winds with less variability).…”
Section: Weibull Distributionmentioning
confidence: 95%
See 1 more Smart Citation
“…The parameter c, in general, was close to 3 ms -1 (10 m) and 4 ms -1 (100 m). Analyses carried out by Ramos et al (2018) show distribution patterns as positive examples for eolic energy generation, as they detect only minor problems with the change of the wind (winds with less variability).…”
Section: Weibull Distributionmentioning
confidence: 95%
“…However, the values are low when compared to results for the Northeast region of Brazil. Ramos et al (2018) found sites in the Northeast (Alagoas State) during the dry season with WPD values around 700 W m -2 , and even during the rainy season, 400 Wm -2 . However, it is important to highlight that the Northeast has wind speeds higher than 8 ms -1 , 2010), but with lower wind intensity and WPD values.…”
Section: Wind Power Density (Wpd)mentioning
confidence: 95%
“…A maioria dos projetos eólicos se desenvolvem com base em modelos numéricos dos atlas eólicos, sendo que o primeiro atlas eólico do Brasil foi publicado em 2001 para 50 m de altura, e, posteriormente, devido ao rápido desenvolvimento da energia eólica no país, foram elaborados atlas eóli-cos estaduais para cada região do Brasil, que podem ser consultados na página do Centro de Referência para Energia Solar e Eólica Sérgio de Salvo Brito (CRESESB, 2019). Após obtido os dados referente ao atlas eólico de interesse, esses dados são validados por medidas coletadas durante o período de apenas um ano (Martins & Pereira, 2011;Ramos et al, 2018), embora somente a partir do ano de 2017 começou-se a exigir um período mínimo de três anos de medições contínuas in situ do vento para que um empreendimento eólico esteja habilitado a participar de leilões de energia, sendo que antes do ano de 2009 as medições anemométricas sequer eram obrigatórias segundo a Empresa de Pesquisa Energética (EPE, 2018). O mapeamento do potencial eólico no Brasil a 50 m de altura para diferentes condições de terreno realizado através de modelagem numérica pode ser visto em Feitosa et al (2003).…”
Section: Introductionunclassified
“…Geralmente, a geração elétrica se inicia com velocidades do vento da ordem de 3,0 m.s -1 (Costa & Lyra, 2012). Para o NEB, os primeiros trabalhos que analisaram dados de vento acima do nível padrão de 10 m foram o de Costa & Lyra (2012) e Ramos et al (2018), ambos para o estado de Alagoas. No primeiro estudo, os autores analisaram as características do vento em regiões distintas do estado na altura de 30 m. No segundo estudo, os autores analisaram o comportamento sazonal e o ciclo diurno do vento no nível de 50 m utilizando a distribuição de Weibull (Takle et al, 1978).…”
Section: Introductionunclassified
See 1 more Smart Citation